Prática de Mindfulness no Sistema Prisional - Pedrette, Washington Luis [UNIFESP] (2020)
Understand how the practice of mindfulness can influence quality of life and emotional self-regulation, in subjects in the prison system. Objective : this study aimed to understand interventions based on mindfulness in the prison system. Method: an integrative literature review was carried out using the mindfulness descriptors in the prison system in the Pub med and Lilacs, Scielo research bases. Results : 8 studies were found that include the inclusion criteria. The studies showed that the practice of mindfulness in the prison system promotes quality of life, with better coping with stress, emotional self regulation, showing improvements in anger control, and improvements in cognitive performance and emotional self-regulation. Conclusion: The practice of mindfulness in the prison system proved to be very promising in the treatment of traumas, although the prison system has variables that hinder the research methodology due to the length of time, adequate space and the support of the prison system. need for research that deepens the investigation to study the effects of meditation on subjects in conditions of incarceration, with an experimental appropriate and adapted to the prison context.